Techno-Economic Analysis of NH3 Fuel Supply and Onboard Re-Liquefaction System for an NH3-Fueled Ocean-Going Large Container Ship - Jinkwang Lee; Younseok Choi; Jungho Choi (Journal of Marine Science and Engineering, 2022)
This study proposed the integrated design of an NH3 fuel supply system and a re-liquefaction system for an ocean-going NH3-fueled ship. The target ship was a 14,000 TEU large container ship traveling from Asia to Europe. The NH3 fuel supply system was developed to feed the liquid fuel at 40 °C and 80 bar and cope with the re-circulated fuel with the sealing oil. Its power consumptions and SECs ranged from 56.4 to 157.5 kW and from 0.0063 to 0.009 kWh/kg, respectively. An onboard re-liquefaction system with a vapor compression refrigeration cycle was also designed to liquefy the BOG from the fuel tank. The re-liquefaction system’s exergy efficiency and SEC were 34.71% and 0.224 kWh/kg, respectively. The equipment with the most exergy destruction was the heat exchangers, accounting for 60% of the total exergy destruction. NPV analysis found that it is recommended to introduce the re-liquefaction system to the target ship. At the NH3 price of USD 250/ton, the reasonable cost of the re-liquefaction system is less than USD 1 million. According to LCC, NH3 fuel is economically feasible if the carbon tax is more than USD 80/ton and the NH3 price is around USD 250/ton.